National Home and Hospice Care Survey, 1998 ([Verlag nicht ermittelbar], 2005)
The National Home and Hospice Care Survey (NHHCS) for 1998 examines home health agencies and hospices and their current patients and discharges. These surveys were designed to provide information for those who establish standards for, plan, provide, and assess long-term care services, both in the home and in inpatient settings. Data on agency characteristics were obtained through personal interviews with the agency administrators and include the number of home health and hospice patients served in the last 12 months, type of facility ownership (i.e., profit, nonprofit, government, other), Medicare and Medicaid certification, number and type of staff, and the hours they worked. Data on a sample of patients currently receiving home health and hospice care as well as a sample of discharges were obtained by interviewing staff persons most familiar with the care provided to these patients. Respondents were requested to refer to medical or other records whenever necessary. No patient was interviewed directly. Information for patients currently receiving services and discharged patients includes services provided and provider type, type of residence, referral source, medical diagnosis, type of care (home health or hospice), type of aids used (eyeglasses, dentures, walker, cane, oxygen, hospital bed, etc.), daily living activities that required assistance, and billing charges and expected payment source(s). The discharge diagnosis for discharged patients was also recorded. Demographic variables for both types of patients include sex, age, race, Hispanic origin, and marital status.